Review of Islamic Law on Halal Food Products in an Effort to Protect Consumers in Surakarta City - Habib, Muhamad; Mustofa, Khoirul; Amallia, Sabrina Difa; Izzatul, Munira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The development of food and beverages sold and bought and sold more and more in the current era. This makes consumers free to choose whatever food they like, but as smart consumers must be careful and careful in consuming the goods consumed. Halal labeling is an important item in products that become the main preference for consumers, especially for Muslim consumers to purchase products even though sometimes only limited to the intention to buy. One of the largest Muslim consumers is in Surakarta City. A perspective review of Islamic law needs to be carried out to protect consumers against the products they consume. The urgency of this research makes it important for this research to be carried out so that consumers and producers understand each other correctly about the concept of labeling from the perspective of Islamic law and positive law. This study aims to determine the review of Islamic law on halal restaurant products, as well as determine the influence of halal labeling on purchasing decisions for public consumption products in Surakarta City.